Observations on overwintering of Agrotis ipsilon (Hufnagel) in different Italian regions (Bollettino di zoologia agraria e bachicoltura, 2024)
In the framework of a research project carried out for several years about the outbreaks of Agrotis ipsilon (Hufnagel) (Lepidoptera, Noctuidae) the Authors refer about the overwintering of the species. An open field·rearing was carried out in order to evaluate the survival rate during the winter in northern (Veneto region) and southern Italy (Campania region). In the Veneto region the reduced winter survival appeared to be linked to the number of hours with a temperature lower 0°C and frozen soil, while the survival rate in Campania region was higher. After the experimental data, the Authors conclude that the irregular outbreaks of the Noctuid, in northern Italy in particular, can usually be ascribed to the oviposition of migrant females at the beginning of spring.
Keywords: Noctuids; Agrotis ipsilon; overwintering; North-eastern and South Italy